Third Person Perceptions About the Ability to Detect Fake News: The Role of Media Diet and Conspiracy Theories - Corbu, Nicoleta; Buturoiu, Raluca; Oprea, Denisa-Adriana (Calitatea Vieții, 2022)
Multiple forms of disinformation have proliferated on digital media platforms during the COVID-19 pandemic, when news consumption increased considerably. In this specific context, this paper investigates the way media diet influences the third person perceptions about people’s ability to detect fake news. We focus here on some understudied predictors of third person perception about fake news detection, such as diversity of media diet and belief in conspiracy theories. By means of a national survey (N=1006) conducted in Romania in October 2020, we test this effect for close and distant others, and the role both mainstream and online media play in this context. Main findings show that frequency of news consumption, trust in the media, and belief in conspiracy theories decrease the perceptual gap between self and others, while education and the diversity of the media diet intensifies it.